Adaptive potential of oat accessions in the context of their chemical and physical grain characteristics - V. I. Polonskiy; S. А. Gerasimov; A. V. Sumina; S. A. Zute (Труды по прикладной ботанике, генетике и селекции, 2022)
Providing high and stable grain harvests with high content of valuable compounds in grain is an important task of crop production. The aim of the study was to assess the adaptability of oat accessions through the analysis of their chemical and physical properties and disclose relationships among adaptability indicators based on these characteristics.Eighteen oat accessions from the VIR collection, grown for 3 years in Eastern Siberia, were assessed. The content of β-glucans and oil, 1000 grain weight, and test weight were analyzed. Four adaptability indicators were measured for the aforesaid characters.Plasticity and stability parameters of the accessions showed no significant differences between the naked and hulled oat forms. Cvs. ‘Sapsan’ (k-15444) and ‘Aldan’ (k-15115) demonstrated the best adaptability in the content of β-glucans in grain, ‘Sayan’ (k-14043) and ‘Vyatsky’ (k-14960) in oil content, ‘Korifey’ (k-15113) and ‘Taidon’ (k-15183) in 1000 grain weight, and ‘Korifey’ and ‘Gosha’ (к-15120) in their test weight. Among the naked oat accessions, significant relationships were recorded between the adaptability indicators of the content of β-glucans or oil in grain and those of the test weight as well as between the average 1000 grain weight of the accessions and the parameters of their plasticity (negative correlations) or stability (positive correlations) for the said physical character.There is a high risk of obtaining hulled oats with reduced levels of oil in their grain, when selected for high stability for this character. It is assumed that successful oat breeding for increased adaptability in 1000 grain weight will be accompanied by an increase in grain size. The possibility of indirect estimation of the adaptability of naked oat accessions according to their β-glucan or oil content is shown on the basis of calculating their adaptability according to the test weight of their grain.